Nanosizing Approaches: Current Trends in the Solubility Enhancement of Poorly Water-soluble Drugs - Shilpi, Satish; Gurnany, Ekta; Bhatt, Shvetank; Gupta, Pawan K; Sethiya, Neeraj K; Jain, Vikas; Jain, Rupshee (Indian Journal of Pharmaceutical Education and Research, 2023)
Nanosuspension formulation and production techniques are currently undergoing remarkable growth in pharmaceutical industries to address poor aqueous solubility and low bioavailability of active pharmaceutical ingredients. It has some distinct character and benefits over other methodologies used to enhance aqueous solubility. The controlled process including formulation and processing variables provide the requisite shape and size of the drug particles in the form of nanosuspension. Generally, drug particles in the form of nanosuspension can be obtained in the size range of 200 to 1000 nm by manipulating various parameters. The pharmacokinetic parameters of the drugs can also be altered by changing the size of drug particles by developing them in the form of nanosuspension. The current review aims to address the physico-chemical characteristics of nanosuspensions, including various formulation considerations. This review also includes potential applications and recent advancements in the field of nanosizing technology.
Keywords: Nanoparticles; Nanosuspension; Nanosizing approaches; Saturation solubility; Pharmacokinetics